Hematopoietic Stem Cell Transcription Factors in Cardiovascular Pathology - Duddu, Sushmitha; Chakrabarti, Rituparna; Ghosh, Anuran; Shukla, Praphulla Chandra (Frontiers in Genetics, 2020)
Transcription factors as multifaceted modulators of gene expression that play a central role in cell proliferation, differentiation, lineage commitment, and disease progression. They interact among themselves and create complex spatiotemporal gene regulatory networks that modulate hematopoiesis, cardiogenesis, and conditional differentiation of hematopoietic stem cells into cells of cardiovascular lineage. Additionally, bone marrow-derived stem cells potentially contribute to the cardiovascular cell population and have shown potential as a therapeutic approach to treat cardiovascular diseases. However, the underlying regulatory mechanisms are currently debatable. This review focuses on some key transcription factors and associated epigenetic modifications that modulate the maintenance and differentiation of hematopoietic stem cells and cardiac progenitor cells. In addition to this, we aim to summarize different potential clinical therapeutic approaches in cardiac regeneration therapy and recent discoveries in stem cell-based transplantation.